INTEGRATIVE CARE DYNAMICS: EXPLORING THE INTERPLAY BETWEEN SOCIAL WORK AND NURSING PRACTICES - Afaf Hamad Aldhafeeri, Nawal Reja AL Dhafeeri, Nasrah Hamad Aldhafeeri, Dalal Munawir AL Dhafeeri, Albannat Munayjil Aljameeli, Maryam Ayyadah AL Dhafeeri, Muneera Rabee Farhan Aldhofeery, (Chelonian Research Foundation, 2022)
This study aimed to explore the interplay between social work and nursing practices in the context of integrative care. A mixed-methods approach was employed, combining a cross-sectional survey of 312 social workers and nurses in healthcare settings across Saudi Arabia with semi-structured interviews of 20 purposively selected participants. Quantitative data were analyzed using descriptive statistics, t-tests, and multiple linear regression, while qualitative data were analyzed using thematic analysis. The findings revealed a significant positive relationship between interprofessional collaboration and patient outcomes, with social workers and nurses reporting high levels of collaboration and job satisfaction. Key themes emerging from the interviews included the importance of effective communication, mutual respect, and shared decision-making in facilitating integrative care. The study highlights the need for ongoing interprofessional education and organizational support to promote collaborative practice and optimize patient care.